2016
DOI: 10.1093/scan/nsw120
|View full text |Cite
|
Sign up to set email alerts
|

Ventral striatum and amygdala activity as convergence sites for early adversity and conduct disorder

Abstract: Childhood family adversity (CFA) increases the risk for conduct disorder (CD) and has been associated with alterations in regions of affective processing like ventral striatum (VS) and amygdala. However, no study so far has demonstrated neural converging effects of CFA and CD in the same sample. At age 25 years, functional MRI data during two affective tasks, i.e. a reward (N = 171) and a face-matching paradigm (N = 181) and anatomical scans (N = 181) were acquired in right-handed currently healthy participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 82 publications
(128 reference statements)
4
49
0
6
Order By: Relevance
“…However, that harsh parenting was related to lower amygdala reactivity to fearful facial expressions contrasts with our hypotheses and previous studies among adolescents, in which child maltreatment (8) and social deprivation (9) predicted greater amygdala reactivity to angry and fearful facial expressions relative to calm faces, respectively. However, a recent paper using a sample at risk for AB reported that greater childhood family adversity also predicted blunted amygdala reactivity to emotional facial expressions (49), consistent with our results. Thus, it could be that the differences in directionality between our findings and the maltreatment literature (8, 9) are due to sample characteristics including the prevalence of AB and the all-male nature of our sample, with boys being at greater risk for AB (22,48).…”
Section: Discussionsupporting
confidence: 92%
“…However, that harsh parenting was related to lower amygdala reactivity to fearful facial expressions contrasts with our hypotheses and previous studies among adolescents, in which child maltreatment (8) and social deprivation (9) predicted greater amygdala reactivity to angry and fearful facial expressions relative to calm faces, respectively. However, a recent paper using a sample at risk for AB reported that greater childhood family adversity also predicted blunted amygdala reactivity to emotional facial expressions (49), consistent with our results. Thus, it could be that the differences in directionality between our findings and the maltreatment literature (8, 9) are due to sample characteristics including the prevalence of AB and the all-male nature of our sample, with boys being at greater risk for AB (22,48).…”
Section: Discussionsupporting
confidence: 92%
“…The face matching task used here has been widely used in both the fMRI (e.g., Burkhouse et al, 2016; Hariri, Tessitore, Mattay, Fera, & Weinberger, 2002; Holz et al, 2017; Prater, Hosanagar, Klumpp, Angstadt, & Phan, 2013) and LPP (Kujawa et al, 2015; MacNamara et al, 2016, 2013) literatures, with shapes commonly employed as a control condition (as in the current study). As such, results reported here represent some of the first “crosstalk” between these otherwise relatively independent literatures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences between the present results and prior work may reflect a combination of the different types of analyses used and the wider range of psychiatric symptomatology in the present sample. The face-matching task used here has been widely used in both the fMRI (e.g., Burkhouse et al, 2017;Hariri et al, 2002;Holz et al, 2017;Prater, Hosanagar, Klumpp, Angstadt, & Phan, 2013) and LPP (Kujawa et al, 2015;MacNamara et al, 2013 literatures, with shapes commonly employed as a control condition (as in the current study). As such, results reported here represent some of the first "crosstalk" between these otherwise relatively independent literatures.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adolescents, CM is linked to both reductions (Edmiston et al, 2011;Mehta et al, 2009) and increases in amygdala volume (Holz et al, 2016;Morey et al, 2016;Sarah Whittle et al, 2009). Along the same lines, a recent meta-analyses suggest no amygdala alterations in healthy individuals with a history of CM (Calem, Bromis, McGuire, Morgan, & Kempton, 2017;Paquola et al, 2016), and amygdala volume did not mediate the link between CM and behavioural problems (Hanson, Nacewicz, et al, 2015).…”
Section: Brain Structurementioning
confidence: 99%
“…McCrory, De Brito, & Viding, 2011;E. J. McCrory et al, 2013;Olsavsky et al, 2013;Suzuki et al, 2014;N Tottenham et al, 2011;Van Harmelen et al, 2013) and altered striatal reward processing (Boecker et al, 2014;Dillon et al, 2009;Hanson, Hariri, & Williamson, 2015;Holz et al, 2016;Philip et al, 2016). Furthermore, CM has been associated with altered activity in, as well as functional connectivity between, PFC regions associated with stress response and emotion regulation (Bruce et al, 2013;Gregory A. Fonzo, Huemer, & Etkin, 2016;Jankowski et al, 2016;Lim et al, 2015;Mueller et al, 2010;Vanessa B Puetz et al, 2014;S J A van der Werff et al, 2012;van Harmelen, Hauber, et al, 2014;van Harmelen, van Tol, et al, 2014).…”
Section: Brain Functioningmentioning
confidence: 99%